Sex Differences in Screen Time and Playfulness among Chinese Preschool Children - et. al., Ju Ern Tun, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Past researches showed that there are sex differences in screen time and playfulness and it does affect children’s development. The purpose of the present study is to determine the sex differences in screen time and playfulness among Chinese preschool children in Kuala Lumpur. There were 217 mothers of Chinese preschool children aged between four to six years old study at selected private preschools in Kuala Lumpur were recruited as respondents in this study by using Stratified Proportionate Random Sampling technique. Self-administered questionnaire was distributed to mothers. Children’s screen time was assessed by using Screen Time Questionnaire (STQ), whereas the information of playfulness was collected by using Child Behavior Inventory of Playfulness (CBI). All instruments used in the current study showed good reliability in the local context with overall reliability score of above .70. Independent t-test was used to determine the gender differences in screen time and playfulness. As the results, there was no significant gender difference in screen time (t = -1.25, p > .05) and playfulness (t = -1.46, p > .05). In sum, the study provides valuable information about screen time and playfulness among male and female preschool children.